In vivo human corneal deformation analysis with a Scheimpflug camera, a critical review. Issue 5 (12th February 2016) - Lanza, Michele; Iaccarino, Stefania; Bifani, Mario
Abstract : Corneal morphological analysis has greatly improved in recent years, providing physicians with new and reliable parameters to study. Moreover, today corneal functional too is a routine analysis, thanks to biomechanical evaluation allowed by an ocular response analyzer (Reichert Ophthalmic Instrument, Depew, NY, USA). Corvis ST (OCULUS Optikgeräte GmbH, Wetzlar, Germany), that relies on the ultrahigh speed Scheimpflug camera, is a new device providing corneal deformation parameters measured ny scanning the cornea response to an air puff; it is an instrument able to measure intraocular pressure too. This device could open up a whole new prospective in screening, detecting and managing corneal diseases, intraocular pressure measurement and in evaluating surgical procedures involving the cornea. This paper provides a comprehensive explanation of Corvis ST measurement principles and parameters and a literature review of scientific studies. Abstract : This review provides a complete and deep analysis of the most recent papers evaluating the new device for corneal deformation detection: Corvis ST (Oculus Optikgeräte GmbH, Wetzlar, Germany). Particular attention has been paid in comparison of results of research about the same group of patients (healthy eyes, keratoconus ones, glaucoma ones, refractive surgery ones etc), in order to let the reader better understand the innovation and the utilities that this device is able to provide. Section about new, experimental, prospectives has been added.